Training on Teaching Material Development Using Artificial Intelligence for Lecturers and Teachers of Muhammadiyah Schools in East Kalimantan: Pelatihan Pembuatan Bahan Ajar dengan Pemanfaatan Artificial Intelegence bagi Dosen dan Guru Sekolah Muhammadiyah di Kalimantan Timur - Rachman , Dzul; Khatimah, Khusnul; Halim, Abdul (Journal of Empowerment and Community Service (JECSR), 2024)
Education must also keep pace with the times. In the development of human life, technology plays a crucial supporting role, as it has become immensely beneficial to humanity. This training will use an interactive workshop approach that combines theory, practice, and mentorship. From the community service activities conducted, it can be concluded that the training on creating AI-based teaching modules and learning media for teachers has yielded effective results, as all targets were successfully met. This initiative also received a highly positive response from the participating teachers, evident from their enthusiasm and the widespread adoption of AI to support learning in the technology implementation phase. Through this training, teachers have also been greatly assisted in improving efficiency, both in administrative tasks and in developing learning media.